(untitled) (Veterinary Science, 2017)
The massive and indiscriminate use of antimicrobials brings abaut some negative consequences like the generation of resistant bacterial strains. Considering the need to get new therapeutic alternatives and having presented the idea that plants are active constituents reservoir not totally studiend yet, a primary screening was performed in 80 of the vegetable extracts coming from wild plants collected in different geographic areas in the province of La Pampa. The purpose was to detect new sources of animicrobial agents, 41.25% of the vegetable species showed an inhibition zone against Staphylococcus aureus